In silico analysis of proteins and microRNAs related to human African trypanosomiasis in tsetse fly. (October 2020) - Yang, Zhiyuan; Wang, Mingqiang; Zeng, Xi; Wan, Angel Tsz-Yau; Tsui, Stephen Kwok-Wing
Graphical abstract: Highlights: We have re-annotated the genome of tsetse fly and identified novel miRNAs based on a series of reliable bioinformatics tools. 25 proteins and 35 miRNAs were found to be associated with trypanosome survival. Two miRNAs (miR-619-5p and miR-2490-3p) were observed to target several critical genes that participated in the infection of human African trypanosomiasis. Ten miRNAs were found to be unique in tsetse fly compared to other insects. Abstract: Human African trypanosomiasis (HAT), also known as sleeping sickness, causes millions of deaths worldwide. HAT is primarily transmitted by the vector tsetse fly ( Glossina morsitans ). Early diagnosis remains a key objective for treating this disease. MicroRNAs (miRNAs) are evolutionarily conserved small non-coding RNAs that play key roles in vector-borne diseases. To date, the roles of proteins and miRNAs in HAT disease have not been thoroughly elucidated. In this study, we have re-annotated the function of protein-coding genes and identified several miRNAs based on a series of bioinformatics tools. A batch of 81.1 % of tsetse fly proteins could be determined homology in mosquito genome, suggesting their probable similar mechanisms in vector-borne diseases. A set of 11 novel salivary proteins and 14 midgut proteins were observed in the tsetse fly, which could be applied to the development of vaccine candidates for the control of HAT disease. In addition, 35 novel miRNAs were identified, among which 10 miRNAs were found to be unique in tsetse fly. Pathway analysis of these 10 miRNAs indicated that targets of miR-15a-5p were significantly enriched in the HAT-related neurotrophin signaling pathway. Besides, topological analysis of the miRNA-gene network indicated that miR-619-5p and miR-2490-3p targeted several genes that respond to trypanosome infection, including thioester-containing protein Tep1 and heat shock protein Hsp60a. In conclusion, our work helps to elucidate the function of miRNAs in tsetse fly and establishes a foundation for further investigations into the molecular regulatory mechanisms of HAT disease.